Explaining Echis: Proteotranscriptomic Profiling of Echis carinatus carinatus Venom - Salil Javed; Prasad Gopalkrishna Gond; Arpan Samanta; Ajinkya Unawane; Muralidhar Nayak Mudavath; Anurag Jaglan; Kartik Sunagar (Toxins, 2025)
Snakebite remains the most neglected tropical disease globally, with India experiencing the highest rates of mortality and morbidity. While most envenomation cases in India are attributed to the ‘big four’ snakes, research has predominantly focused on Russell’s viper (Daboia russelii), spectacled cobra (Naja naja), and common krait (Bungarus caeruleus), leading to a considerable gap in our understanding of saw-scaled viper (Echis carinatus carinatus) venoms. For instance, the venom gland transcriptome and inter- and intra-population venom variation in E. c. carinatus have largely remained uninvestigated. A single study to date has assessed the effectiveness of commercial antivenoms against this species under in vivo conditions. To address these crucial knowledge gaps, we conducted a detailed investigation of E. c. carinatus venom and reported the first venom gland transcriptome. A proteotranscriptomic evaluation revealed snake venom metalloproteinases, C-type lectins, L-amino acid oxidases, phospholipase A2s, and snake venom serine proteases as the major toxins. Moreover, we assessed the intra-population venom variation in this species using an array of biochemical analyses. Finally, we determined the venom toxicity and the neutralising efficacy of a commercial antivenom using a murine model of snake envenoming. Our results provide a thorough molecular and functional profile of E. c. carinatus venom.